Comprehensive Case Study On Harta Packaging Industries Sdn Bhd - Long, Lim Ong (2002)
This paper traces the history of Harta, the internal and external environments in which it operates, its strenghts, weaknesses, opportunities and threats and finally the proposed strategies to be employed in its core competencies to reposition itself in the packaging industry.